Burden of hypertension and associated risks for cardiovascular mortality in Cuba: a prospective cohort study. (February 2019) - Armas Rojas, Nurys; Dobell, Emily; Lacey, Ben; Varona-Pérez, Patricia; Burrett, Julie Ann; Lorenzo-Vázquez, Elba; Calderón Martínez, Marcy; Sherliker, Paul; Bess Constantén, Sonia; Morales Rigau, José Manuel; Hernández López, Osvaldo Jesús; Martínez Morales, Miguel Ángel; et al.
Summary: Background: In Cuba, hypertension control in primary care has been prioritised as a cost-effective means of addressing premature death from cardiovascular disease. However, there is little evidence from large-scale studies on the prevalence and management of hypertension in Cuba, and no direct evidence of the expected benefit of such efforts on cardiovascular mortality. Methods: In a prospective cohort study, adults in the general population identified via local family medical practices were interviewed between Jan 1, 1996, and Nov 24, 2002, in five areas of Cuba, and a subset of participants were resurveyed between July 14, 2006, and Oct 19, 2008, in one area. During household visits, blood pressure was measured and information obtained on diagnosis and treatment of hypertension. We calculated the prevalence of hypertension (systolic blood pressure ≥140 mm Hg or diastolic blood pressure ≥90 mm Hg, or receiving treatment for hypertension) and the proportion of people with hypertension in whom it was diagnosed, treated, and controlled (systolic blood pressure <140 mm Hg, diastolic blood pressure <90 mm Hg). Deaths were identified through linkage by national identification numbers to the Cuban Public Health Ministry records, to Dec 31, 2016. We used Cox regression analysis to compare cardiovascular mortality between participants with versus without uncontrolled hypertension. Rate ratios (RRs) were used to estimate the fraction of cardiovascular deaths attributable to hypertension. Findings: 146 556 participants were interviewed in the baseline survey in 1996–2002 and 24 345 were interviewed in the resurvey in 2006–08. After exclusion for incomplete data and age outside the range of interest, 136 111 respondents aged 35–79 years (mean age 54 [SD 12] years; 75 947 [56%] women, 60 164 [44%] men) were eligible for inclusion in the analyses. 34% of participants had hypertension. Among these, 67% had a diagnosis of hypertension. 76% of participants with diagnosed hypertension were receiving treatment and blood pressure was controlled in 36% of those people. During 1·7 million person-years of follow-up there were 5707 cardiovascular deaths. In the age groups 35–59, 60–69, and 70–79 years, uncontrolled hypertension at baseline was associated with RRs of 2·15 (95% CI 1·88–2·46), 1·86 (1·69–2·05), and 1·41 (1·32–1·52), respectively, and accounted for around 20% of premature cardiovascular deaths. Interpretation: In this Cuban population, a third of people had hypertension. Although levels of hypertension diagnosis and treatment were commensurate with those in some high-income countries, the proportion of participants whose blood pressure was controlled was low. As well as reducing hypertension prevalence, improvement in blood pressure control among people with diagnosed hypertension is required to prevent premature cardiovascular deaths in Cuba. Funding: Medical Research Council, British Heart Foundation, Cancer Research UK.